Nightbird [compact disc, unabridged] - Hoffman, Alice (Listening Library, 2015)
Twig, aged twelve, is practically ignored by classmates and other residents of Sidwell, Massachusetts, but gets along fine with just her mother and brother, whose presence must be kept secret, until descendants of the witch who cursed her family move in next door and want to be her friends.